Safety of powerlifting: A literature review - Dudagoitia, E.; García-de-Alcaraz, A.; Andersen, L. L. (Science & Sports, 2021)
Objective While powerlifting is a popular sport, there may be some safety concerns due to the repeated high loads. This literature review focuses on injury rates, areas of injury and biomechanical movement analysis.